RESEARCH OF RELIABILITY CALCULATION METHODS OF PIPELINE SYSTEMS - Гавриленко, Ирина Александровна (Eastern-European Journal of Enterprise Technologies, 2012)
This article covers reliability calculation methods regarding pipeline systems. Advantages and defects of reliability calculation methods of pipeline systems are determined.